Penggunaan Media Kuartet Cerdas untuk Meningkatkan Hasil Pembelajaran PKN di SD - Widi Nursyamsi Apriawan; Nana Ganda; Syarip Hidayat (STKIP Andi Matappa Pangkep, 2021)
The learning outcomes of fourth grade students at SDN 2 Sadapaingan, Panawangan District, Ciamis Regency, in understanding the meaning of the relationship between symbols and the Pancasila precepts are still low. This is because the learning interactions delivered by the teacher do not use the right media, so to overcome these problems, the